MANFAAT ASURANSI SAMPAH BAGI PENINGKATAN KESEJAHTERAAN MASYARAKAT - Mutiara Ayu Putri; Ida Nuraini; Muhammad Sri Wahyudi Suliswanto (Jurnal Ilmu Ekonomi JIE, 2019)
This research is aimed at knowing the characteristics of member garbage insurance in Malang and the differences based on the level of cost treatment pre-and post-the garbage insurance exist. Descriptive quantitative method was used in this research and analyzed by using different test with SPSS application. The result revealed that by the existence of garbage insurance could chage the health facility in Lowokwaru district. Moreover, the public health increased, so it gave different health care cost which was significant. The differences of health care cost between pre and post the garbage insurance exist are amount 1.730.000 Rupiah. Means, every garbage insurance member on average only experience decreasing cost treatment amount 5.151 Rupiah.